2021
DOI: 10.3390/ijerph18157981
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Color Perception and Preference with Eye-Tracking Analysis in a Dental Treatment Environment

Abstract: Nowadays, medical facilities are developing their treatment environment to provide better services to their patients. In particular, dental hospitals have been considered uncomfortable and uninviting spaces, which needs to change so that people can visit easily and feel more relaxed. However, only a few systematic studies have reported on the demand for building a comfortable space. This study aimed to investigate gaze characteristics based on a color preference survey of the dental unit chair, which has the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Chen et al pointed out that people prefer to look at trees rather than buildings in outdoor activities [30]. Song investigated color preferences in dental hospitals and found that brown stabilized patients more effectively than the traditional blue [31]. Zhang discovered that subway rooms with too much or too little color saturation and brightness might be unsettling, and the most popular colors are not always the most visually pleasing for people [13].…”
Section: Application Of Eye-tracking Technology In the Design Of Publ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al pointed out that people prefer to look at trees rather than buildings in outdoor activities [30]. Song investigated color preferences in dental hospitals and found that brown stabilized patients more effectively than the traditional blue [31]. Zhang discovered that subway rooms with too much or too little color saturation and brightness might be unsettling, and the most popular colors are not always the most visually pleasing for people [13].…”
Section: Application Of Eye-tracking Technology In the Design Of Publ...mentioning
confidence: 99%
“…Subjects were instructed to sit 70 cm in front of the eye-tracking device. Before undertaking the eye movement experiment to see the photos, subjects were only instructed to relax, and the experiment's goal was not apparent [31]. Before starting the formal experiment, a five-point calibration method controlled the subject's line of sight shift to within 0.5 • .…”
Section: Eye Movement Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the monitor should move stably and smoothly, and should be supported and fixed stably even after the movement without any motion. A legible resolution is needed in the treatment process for the display of radiographs, oral photographs, and texts [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A dental unit chair is a necessity in dental clinics, but due to the continuous development of the dental medical device market, various dental unit chairs are being developed, making it difficult for dentists to properly select a dental unit chair when purchasing the dental unit chair. The dental unit chair causes eye fatigue due to light [ 8 , 9 ]; should feature an appropriate size and angle of the patient seat [ 10 , 11 , 12 , 13 ], and the appropriate usability of the foot controller [ 14 , 15 ]; the water fountain and cuspidor should be convenient [ 16 , 17 ]; and there should be harmony between the monitor and the overall treatment system [ 21 , 22 ], as well as size and stability of bracket table and controller [ 23 , 24 ]. It is selected by various factors, including the overall design [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%